2004
DOI: 10.1111/j.1365-2222.2004.02101.x
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol during pregnancy and atopic dermatitis in the offspring

Abstract: The results suggest that alcohol during pregnancy increases the risk of early-onset AD in predisposed infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
58
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(60 citation statements)
references
References 33 publications
1
58
1
Order By: Relevance
“…In a recent report evaluating a Japanese cohort, maternal alcohol intake during pregnancy significantly increased the risk of atopic eczema before age 3 and before age 5. 49 These data are in agreement with other authors, who demonstrated an increased risk of atopic dermatitis in early infancy 50 and during the first 7 years of life in alcohol-exposed offspring. 51 Nevertheless, the data on foetal alcohol’s effect on the development of asthma is less convincing.…”
Section: Foetal Alcohol Exposure and Risk Of Adverse Pulmonary Outcomessupporting
confidence: 91%
“…In a recent report evaluating a Japanese cohort, maternal alcohol intake during pregnancy significantly increased the risk of atopic eczema before age 3 and before age 5. 49 These data are in agreement with other authors, who demonstrated an increased risk of atopic dermatitis in early infancy 50 and during the first 7 years of life in alcohol-exposed offspring. 51 Nevertheless, the data on foetal alcohol’s effect on the development of asthma is less convincing.…”
Section: Foetal Alcohol Exposure and Risk Of Adverse Pulmonary Outcomessupporting
confidence: 91%
“…Several epidemiological studies have linked alcohol consumption to IgE sensitization against inhalant allergens, but only 1 of these was prospective [12,13,14,15,16]. Furthermore, maternal alcohol consumption during pregnancy has been linked to early atopic phenotypes (cord blood IgE and early-onset atopic dermatitis) in the offspring, indicating that alcohol may influence the immune system in utero [17, 18]. One recently published experimental study confirmed the ability of alcohol to induce a marked increase in total serum IgE and suppression of the allergen-specific Th1-dependent IgG response (IgG2a), but in this mouse model with intraperitoneally administered ovalbumin alcohol did not influence the allergen-specific IgE response [19].…”
Section: Introductionmentioning
confidence: 99%
“…Whether fetal alcohol exposure has an effect on allergic disease development is contentious [4244], possibly being confounded by other environmental stimuli. Maternal obesity before or during pregnancy has been reported to increase risk of childhood asthma [45].…”
Section: Dna Methylation and Allergic Diseasementioning
confidence: 99%